PARA SALVAR A NAÇÃO: UMA TEORIZAÇÃO SOBRE EDUCAÇÃO, SAÚDE E RELIGIÃO NA ASSEMBLEIA CONSTITUINTE DE 1934 - OLIVEIRA, RAFAEL DE SOUZA (2018)
This study aims to present a substantive theory about the relation between education, religion and health in the 1934 Constituent Assembly, contributing with other initiatives in the search for ways that help the effective implementation of the public policies of health promotion in Brazilian schools. To this end, it adopts a qualitative method called Grounded Theory, which uses a set of procedures for inductively develop a theory grounded on data collected and analyzed systematically. This method guided the collection of data from the annals of the Constituent, as well as the process of codification and analysis. The software ATLAS.ti® was used as a facilitator tool for coding, writing memos and laying out diagrams. Three macrocategories emerged during the data analysis process: Improving the race, Hygienizing the Nation and Defending Religious Education. At a higher abstract level, as the central category, the category Saving the Nation was obtained. This research reveals eugenism as the agglutinating axis of the proposed triad. The economic backwardness is seen as a result of the inefficiency of the Brazilian people. Such a problem could be overcome, under the eugenic aegis, by solving two major national problems: health and education. In this sense, eugenics, as the incumbency of the State, would be the scientific basis for public policies in these two areas, supported, on the one hand, by hygienism, as an important axiom of health conceptions, and, on the other hand, by the enormous legitimacy and insertion of religious discourse in the population. The role of the Catholic religion, institutionally and by cultural influence, will be decisive for the conformation of the eugenic movement as seen in Brazil. In this context, education is viewed as a privileged way to achieve eugenic ideals.